INCLUSIVE DEMOCRACY: PUBLIC PARTICIPATION IN LEGAL DECISION MAKING IN INDONESIA - Marianata, Anita (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
In implementing the government system, public participation is an important thing. Where, participation doesn’t have an limit who can be involved. Because, a government cannot function as expected if public participation is excluded or if someone who is part of the public is not involved or someone is excluded. If you recall, one of the elements of the founding of a country is the existence of citizens. Citizens of the country as a whole without exception. The research carried out is research by reviewing and using literature or literature studies that are relevant to the situation that occurs in Indonesia as a country that implements the principles of democracy. This research uses qualitative research methods with a descriptive approach. By conducting literature and literature study analysis. As a result of the research conducted, it is known that overall public participation in legislative decision making in Indonesia is still not optimal. There is still a pattern of decision making that does not involve public participation. Public indifference towards the government and legislative policy makers is also part of the public's disappointment with every policy taken. Apart from that, people with disabilities, the elderly, and minority groups, where helplessness is the reason these people isolate themselves and are not involved in any decision making. Decision makers need to pay attention to involving the public from all elements, without anyone being excluded. Of course, this is not an easy thing to implement, but it is also part of the task of state administrators to be able to build public participation in every legislative decision making.